The method of adaptive K-path routing in special purpose wireless networks - Skrypnychenko, A.A. (Problems of Informatization and Management, 2024)
The task of ensuring the end-to-end quality of service of heterogeneous wireless networks (HWNs) with random multiple access is considered. The processes of the emergence of conflicts between the universality and complexity of route selection and resource allocation in BPM are analyzed. A technique for eliminating conflicts between fairness and optimality of resource allocation with different numbers K of routes has been developed. It is shown that with a rational choice of the number of routes, depending on the state and parameters of the autonomous segments and the network as a whole, the functions of each level and, accordingly, the information parameters of the traffic at this level can be attributed to one of two alternative groups: functions that depend on a specific technical implementation networks or application-oriented functions. Accordingly, a global approach to the optimal selection of a radio access technology (RAT) to each of the routes included in the set K is formulated, and an approach to RAT selection using a distributed adaptive search algorithm based on the peak rate at which users are able to receive and transmit is proposed traffic flows. The advantage of the adaptive K-path routing method compared to the classical method was estimated by means of calculations and computer simulations. A distributed system for choosing the number of routes has been developed based on the optimization of the set of routes with the elimination of redundancy.